2017
DOI: 10.1038/s41467-017-01366-x
|View full text |Cite
|
Sign up to set email alerts
|

FBXO32 promotes microenvironment underlying epithelial-mesenchymal transition via CtBP1 during tumour metastasis and brain development

Abstract: The set of events that convert adherent epithelial cells into migratory cells are collectively known as epithelial–mesenchymal transition (EMT). EMT is involved during development, for example, in triggering neural crest migration, and in pathogenesis such as metastasis. Here we discover FBXO32, an E3 ubiquitin ligase, to be critical for hallmark gene expression and phenotypic changes underlying EMT. Interestingly, FBXO32 directly ubiquitinates CtBP1, which is required for its stability and nuclear retention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 70 publications
(109 reference statements)
6
33
0
Order By: Relevance
“…The above data on FBXL5 agrees with previous research in our lab, where we discovered that FBXO32-another F-box protein-was pivotal in upstream EMT regulation not only in tumor metastasis, but in neuronal development also (102). FBXO32 directly ubiquitinated CtBP1 causing its stabilization and nuclear retention, which created a suitable microenvironment for EMT progression by facilitating epigenetic remodeling and transcription of CtBP1 target genes (102). In line with these findings, FBXO32 was amplified in metastatic cancers, and its depletion in vivo inhibited tumor growth and metastasis (102).…”
Section: In Tune With Emt Intracellular Signalingsupporting
confidence: 91%
See 1 more Smart Citation
“…The above data on FBXL5 agrees with previous research in our lab, where we discovered that FBXO32-another F-box protein-was pivotal in upstream EMT regulation not only in tumor metastasis, but in neuronal development also (102). FBXO32 directly ubiquitinated CtBP1 causing its stabilization and nuclear retention, which created a suitable microenvironment for EMT progression by facilitating epigenetic remodeling and transcription of CtBP1 target genes (102). In line with these findings, FBXO32 was amplified in metastatic cancers, and its depletion in vivo inhibited tumor growth and metastasis (102).…”
Section: In Tune With Emt Intracellular Signalingsupporting
confidence: 91%
“…FBXL5/BTG3 are direct miRNA-20a targets that are silenced to enable miRNA-20a-mediated EMT and invasion (99), however the precise role of FBXL5 signaling in EMT requires further research; FBXL5 overexpression reduced Snail protein levels (100), but also supported tumorigenesis by negatively regulated PTEN while promoting PI3K/Akt and mTOR phosphorylation and expression (101). The above data on FBXL5 agrees with previous research in our lab, where we discovered that FBXO32-another F-box protein-was pivotal in upstream EMT regulation not only in tumor metastasis, but in neuronal development also (102). FBXO32 directly ubiquitinated CtBP1 causing its stabilization and nuclear retention, which created a suitable microenvironment for EMT progression by facilitating epigenetic remodeling and transcription of CtBP1 target genes (102).…”
Section: In Tune With Emt Intracellular Signalingsupporting
confidence: 84%
“…The neurodevelopmental phenotypes conferred by the CTBP1 mutant allele provide genetic evidence that CTBP1 is important for normal human brain development. Previous biochemical studies also suggested that CtBPs might be important for certain brain developmental functions (Sahu et al, 2017;Shen et al, 2017). CtBP1 has been reported to mediate transcriptional repression of a number of neuronal genes involved in synaptic activities of the inner ear hair cells, the retina (Ivanova et al, 2015) and the synaptic ribbon complex (Tom Dieck et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no direct relationship between adherent molecules and the expression of α‐E‐catenin and β‐catenin in 3D cultured osteosarcoma cells, indicating that integrin‐AJ mediated tumorigenesis was not tightly associated with ECM adherence. And less adherent molecules conduce to the malignant cancer cells metastasize from situ to secondary focuses . This notion was further verified by in vivo findings showing that α‐E‐catenin expression is not associated with ECM adherence in cancer or even against it.…”
Section: Discussionmentioning
confidence: 82%